Immersive Simulations with Virtual Humans in Higher Education - Ferreira, Joelson Barbosa; Cardoso, Anderson; Specian, Henrique Resende; Silva, Felipe Cortizo E.; da Costa, Julia Gabriela Ferraz; de Lara, Marina; Spricigo, Cinthia Bittencourt (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
This paper presents an analysis of two immersive educational simulators developed at the Pontifical Catholic University of Paraná: SimCom and Mediation VR. SimCom simulates medical consultations using screen-based avatars controlled in real time by students or instructors, while Mediation VR is a virtual reality experience in which law students mediate conflicts between AI-driven avatars. Both tools adopt a role-play approach to foster communication and interpersonal skills. The study examines their pedagogical and technical characteristics and includes qualitative feedback from professors who apply them in the classroom. The findings indicate shared benefits, such as increased student participation and fluency in communication-based tasks, as well as implementation-specific challenges. Based on feedback, SimCom was restructured to improve usability and scalability. For Mediation VR, proposals are outlined to expand expressiveness, enable real-time feedback, and improve customization flexibility. The study reinforces the educational potential of immersive simulators and their adaptability to diverse academic contexts.